COVID-19 Vaccines Side Effects Among Iraqi people In Kurdistan Region: A cross-sectional study - Rebar Yahya Abdullah; Arazoo Issa Tahir; Dlkhosh Shamal Ramadhan; Zuhair Rushdi Mustafa; Kawther Mohammed Galary (OPI Napoli, 2022)
Background: Communities around the world have expressed concern about the safety and side effects of SARS-CoV-2 vaccines. The adverse effects of the Covid-19 vaccines played a critical role in public trust in the vaccines. The current study aimed to provide evidence on the side effects of the BNT163b2 mRNA COVID-19 vaccine (Pfizer-BioNTech®); ChAdOx1 nCoV-19 vaccine (AstraZeneca®); BBIBP-CorVvaccine (Sinopharm®) COVID-19 vaccines. Material and Methods: A cross-sectional study design was performed from April 26th, 2021, to June 3rd, 2021. Convenience sampling was used to select respondents; face validity was performed to the mandatory multiple-choice items questionnaire to cover the respondent's demographic characteristics, coronavirus-19 related anamneses, and the side effect duration of coronavirus-19 vaccines, the data were analyzed by using descriptive statistics. Results: The 588 participants enrolled in the current study. ChAdOx1 nCoV-19 vaccine received 49.7%, followed by BNT163b2 mRNA COVID-19 vaccine and BBIBP-CorV (39.5% and 10.9%). The most common complaint was headache (61.2%), followed by vaccine injection site discomfort (58.8%), fatigue (49.7%), fever (48.3%), muscle discomfort (42.9%), and approximately (10.5% and 10.2%) had injection site swelling and nausea, respectively. Most of those surveyed had postvaccine symptoms for one to two days (25.2%), (41%), and only a small percentage (3.7%) experienced them for over one month. ChAdOx1 nCoV-19 vaccine handled 53% of the side effects, followed by BNT163b2 mRNA COVID-19 vaccine (42%) and BBIBP-CorV vaccines (5%). Conclusion: Prevalence of various local and systemic vaccines side effects, such as headache, fever, and pain at the injection site, was observed. Almost all participants had mild symptoms and were well-tolerated .AstraZeneca® vaccine has the most side effects, followed by the Pfizer® vaccine, and the Sinopharm® vaccine has the least. More independent studies on vaccination safety and public awareness are critical to improving public trust in vaccines.